1994
DOI: 10.1093/oxfordjournals.annonc.a059009
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of early and intermediate stages of supradiaphragmatic Hodgkin's disease: The Swedish National Care Programme Experience

Abstract: The tailored principles, which usually entail less staging and/or treatment than is generally the case, produced favourable results when applied to an entirely unselected group of patients with early and intermediate stages of HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Although, the response of early-stage HD to conventional combined modality therapy had been excellent, [27][28][29][30][31][32] concerns over late effects of therapy on young growing children resulted in efforts to design treatment programs for children and adolescents with HD that would reduce toxicity without jeopardizing response rate and survival. The first step taken by pediatric oncologists to limit toxicity was to reduce the amount of radiation by increased reliance on effective chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although, the response of early-stage HD to conventional combined modality therapy had been excellent, [27][28][29][30][31][32] concerns over late effects of therapy on young growing children resulted in efforts to design treatment programs for children and adolescents with HD that would reduce toxicity without jeopardizing response rate and survival. The first step taken by pediatric oncologists to limit toxicity was to reduce the amount of radiation by increased reliance on effective chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The Stockholm Hodgkin Lymphoma Study Group was established in 1973 23 and national Swedish treatment recommendations for HL were introduced in 1985 and have been updated over the years. [24][25][26] In 1975, the successful use of the combination ABVD (doxorubicin, bleomycin, vinblastine, dacarbazine) was reported, 27 and since the early 1980s, a variety of chemotherapy combinations other than conventional MOPP, including ABVD, MOPP/ABVD, MOPP/ABV (for younger patients), and ChLVPP (chlorambucil, vinblastine, procarbazine, prednisolone), LVPP/OEPA (chlorambucil, vinblastine, procarbazine, vincristine, etoposide, prednisone, doxorubicin), and CHOP (cyclophosphamide, doxorubicin, vincristine, prednisone; mostly elderly patients) were used in previously untreated patients with stage IIB-IV disease. [28][29][30][31][32] Since the 1980s patients with advanced disease reaching a complete remission after 2 cycles traditionally received a total of 6 cycles of chemotherapy.…”
Section: Treatment Principles Of Hl During the Study Periodmentioning
confidence: 99%
“…A drawback of the study is that the Swedish Cancer Register holds no therapy data, but studies have shown that up to 90% of patients were given radiotherapy during our study period (Glimelius et al, 1994, Molin et al, 2003. Many HL patients were probably diagnosed as nonHodgkin's lymphoma (NHL), but because most of them were older patients with a short survival, this will not affect the present results, especially those with long follow-up that are compared with the general population.…”
Section: Risk Of Second Primary Malignancies After Hl a Andersson Et Almentioning
confidence: 92%